Salivary Zinc Level Determination in Patients with Benign Migratory Glossitis - Abbas F Al-Taee (University of Mosul, College of Dentistry, 2012)
Aims: To determine and compare the salivary zinc level concentration (SZLC) and salivary flow rate (SFR) in patient with benign migratory glossitis (BMG) and in control normal subjects, also to evaluate any relationship among these variables in each group. Materials and Methods: The study was con-ducted on 42 individuals who were allocated into two groups: patients group was comprised of 22 pa-tients who did have (BMG) and 20 healthy subjects. Unstimulated whole saliva was collected and both SFR and SZLC were determined. Zinc analysis was performed with an atomic absorption spectropho-tometer. Results: The mean SFR in patients and control groups were 0.5459(ml / min) and 0.6840(ml / min) respectively, whereas the mean SZLC for patients was 0.09764(ppm) and 0.13830 (ppm) for con-trol group. SFR was not differ significantly between both groups (p > 0.099), also SZLC was not sig-nificantly differ in both groups too (p > 0.169). Conclusions: This clinical study could not establish significant association between BMG and both SZLC and SFR.